Kebutuhan Guru dan Siswa dalam Implementasi Pembelajaran STEM–ESD Berbasis AR: Analisis Eksploratori untuk Pengembangan Perangkat Pembelajaran IPAS - Esti Susiloningsih; Apit Fathurohman; Nabilah Mansur (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
The integration of STEM and Education for Sustainable Development (ESD) in Integrated Science and Social Sciences learning remains limited due to conventional teaching methods, low interactivity, and inadequate learning resources, which hinder students’ conceptual understanding and engagement. This study explores the needs of teachers and students in implementing Augmented Reality (AR)–based STEM–ESD learning as a basis for developing effective Integrated Science and Social Sciences learning tools. The study employed an explanatory sequential mixed-methods design, combining quantitative and qualitative data collection. Questionnaires were administered to 24 teachers and 92 students to identify general needs and perceptions, followed by semi-structured interviews with 16 students to obtain deeper insights into their learning experiences and expectations. The results indicate that teachers demonstrate partial readiness in integrating STEM–ESD and prefer AR learning tools that enhance conceptual clarity, provide structured instructional guidance, and align with curriculum competencies. Students reported limited engagement with existing learning materials, difficulties in understanding abstract concepts, and strong interest in AR-supported learning, emphasizing the need for accessible, interactive, and curriculum-relevant media. These findings suggest that AR-based learning tools should prioritize visual clarity, intuitive interfaces, and real-world contextualization to address current instructional gaps. The implications of this study highlight the importance of need-based AR learning design for supporting effective STEM–ESD integration, informing the development of innovative learning tools, and guiding teacher preparation and professional development in implementing technology-enhanced sustainable education.